Iron removal by intermittent coal ash filtration / Hasnul Abd Latif - Abd Latif, Hasnul (1996)
Using coal ash as filter media, a series of test will carried out on waters of high iron concentration level. The dosage will be given intermittently. The efficiencies of such method will be analysed and to be compared with other filter media like sand. The effect of various parameters affecting the removal, such as bed depth, initial concentration of solute, pH etc will be determined. The water quality parameters will be analysed in the influent and effluent waters. It was found dosage time of 9 hours with an interval of 2 days each, gave better performance compared with the 6 and 3 hours dosing time. The pH value of the effluent increased with the existence of hydroxida ion in the media. Intermittent filtration can contribute as an 'aeration1 in filter system whereby increasing the filter performance.